Adaptation of African Swine Virus in Non-Swine Cell Lines: A Preliminary Study for Vaccine Candidate - Tenaya, I Wayan Masa; Agustina, Kadek Karang; Suada, I Ketut; Apsari, Ida Ayu Pasti; Sari, Tri Komala; Handayani, Ni Made; Widayantari, Anak Agung Ayu Sauca Sunia; Suardana, Anak Agung Komang; Sumarya, I Made; Arsana, I Nyoman; Sudiartawan, I Putu; Wahyudi, I Wayan; Juliasih, Ni Ketut Ayu; Sudaryati, Ni Luh Gede; Damriyasa, I Made (Universitas Airlangga, 2025)
African Swine Fever (ASF) is among the most detrimental infectious viral diseases in pigs causing approximately 100% mortality. The disease was first reported about 83 years ago in Africa before spreading to Europe in 1957 and Asia in 2010. An adequate vaccine generally containing live attenuated virus isolates prepared in swine macrophages to control the disease is currently unavailable. Therefore, this study aimed to use murine neuroblastoma (N2a) cells, non-swine cell lines, to adapt African swine fever virus (ASFV) isolates for vaccine preparation. ASFV isolate called BL21 obtained from Bali and East Nusa Tenggara was previously propagated in swine macrophages. However, virus was currently adapted in the N2a cells to avoid unwanted issues associated with using swine macrophages, including microbial contamination, as well as technically laborious and ethical issues. The adapted BL21 was re-confirmed with quantitative polymerase chain reaction (q-PCR) and tested in vivo to examine the pathogenicity properties. The results showed that BL21 produced consistently and specifically positive q-PCR, killing experimental pigs with typical gross pathological changes of ASF. BL21 at a 10-3/mL dilution adapted in N2a cells showed similar antigenic properties causing the death of nearly 50% N2a cells in vitro and terminating all in vivo experimental pigs. In conclusion, the BL21 isolate reported in this study could be used as a vaccine candidate after more attenuation and particularly to determine a lethal dose of 50% (LD50) for future investigations.